Derecho al olvido: Uruguay a la vanguardia de la Protección de Datos Personales - Cervieri, Virginia (2023)
The authors develop a detailed legal framework and scope of the right to erasure in Uruguayan and international legislation, as it is a right that guarantees the protection of personal data, especially in the digital context. In this regard, the authors analyze international legal cases to determine the role of search engines in the treatment of personal data. They also explain how the application of the right to erasure does not affect other rights. Finally, the authors emphasize the importance of using the right to erasure in relation to search engines to ensure adequate protection of personal data.